Antibiotic-induced gut microbiota depletion enhances glucose tolerance linked to GLP-1 signaling - Kellenberger, Alexandra; Dewal, Revati Sumukh; de Wouters d’Oplinter, Alice; Sichert, Andreas; Heine, Markus; Fuh, Marceline M.; Slack, Emma; Delessa Challa, Tenagne; Wolfrum, Christian (Frontiers in Endocrinology, 2025)
IntroductionDepletion of the gut microbiota is known to improve glucose metabolism and modify thermogenic capacity in mice. However, the underlying mechanisms remain unclear. In this study, we aimed to determine whether the browning effect observed after antibiotic treatment contributes to metabolic modifications and to investigate the potential central role of GLP-1 in enhancing glucose metabolism.MethodsUsing an inducible Ucp1DTR mouse model to transiently ablate UCP1+ cells, we assessed glucose tolerance, cold sensitivity, and circulating GLP-1 levels following gut microbiota depletion. We additionally examined GLP-1 levels in germ-free mice. Glucose tolerance was compared to GLP1R KO mice following gut microbiota depletion. Bile acid profiling in wild-type mice treated with antibiotics identified regulated bile acids, which were subsequently tested in an in vitro STC-1 cell assay and in vivo in Cyp2c70 mice to identify potential basal GLP-1 secretion inhibitors.ResultsWe demonstrate that gut microbiota depletion improved glucose tolerance independent of UCP1+ cell presence and increased cold sensitivity. Antibiotic treatment increased circulating active GLP-1 levels within one day, and this increase was also observed in germ-free mice, supporting the suggestion that GLP-1 elevation is driven by gut microbiota depletion. The improvement in glucose tolerance was lost in GLP1R KO mice upon oral glucose ingestion. Bile acid profiling and subsequent validation led to the identification of two potential basal GLP-1 secretion inhibitors.DiscussionOur findings suggest that the metabolic improvements following gut microbiota depletion are primarily driven by GLP-1 signaling, rather than UCP1⁺ cell activation. These results highlight the complex interplay between the gut microbiome and metabolic health, offering insights into potential therapeutic targets for improving glucose metabolism through modulation of basal GLP-1 signaling.